Stimuli-responsive nano vehicle enhances cancer immunotherapy by coordinating mitochondria-targeted immunogenic cell death and PD-L1 blockade - Qiuyi Li; Cheng Chen; Jinxia Kong; Lian Li; Junlin Li; Yuan Huang (Elsevier, 2022)
Induction of immunogenic cell death promotes antitumor immunity against cancer. However, majority of clinically-approved drugs are unable to elicit sufficient ICD. Here, our study revealed that mitochondria-targeted delivery of doxorubicin (DOX) massively amplified ICD via substantial generation of reactive oxygen species (ROS) after mitochondrial damage. The underlying mechanism behind increased ICD was further demonstrated to be ascribed to two pathways: (1) ROS elevated endoplasmic reticulum (ER) stress, leading to surface exposure of calreticulin; (2) ROS promoted release of various mitochondria-associated damage molecules including mitochondrial transcription factor A. Nevertheless, adaptive upregulation of PD-L1 was found after such ICD-inducing treatment. To overcome such immunosuppressive feedback, we developed a tumor stimuli-responsive nano vehicle to simultaneously exert mitochondrial targeted ICD induction and PD-L1 blockade. The nano vehicle was self-assembled from ICD-inducing copolymer and PD-L1 blocking copolymer, and possessed long-circulating property which contributed to better tumor accumulation and mitochondrial targeting. As a result, the nano vehicle remarkably activated antitumor immune responses and exhibited robust antitumor efficacy in both immunogenic and non-immunogenic tumor mouse models.